Desempenho cognitivo de idosas : estresse precoce, encurtamento telomérico e polimorfismo VAL66MET do BDNF - De Nardi, Tatiana de Carvalho (2014)
Aging is a heterogeneous process resulting of biomarkers elicited by multiple factors, such as adverse environment.. A biomarker widely studied as a mediator of aging is the telomeres length. Telomeres are DNA-structures located at the ends of the cells with a protective function. Naturally, It tend to decrease with cell replication, however early life stress (ELS) may accelerate this process promoting premature vulnerability to chronic disease and cognitive decline. In addition, studies suggest that genetic variations such as Val66Met BDNF polymorphism constitute risk condition for memory decline, especially when interacting with aversive environmental conditions. OBJECTIVE: This thesis aimed to investigate the ELS, the Val66Met polymorphism and telomere length effects on the cognitive aging of women. METHOD: three sections are presented: the first, reviewed the neurobiological studies about the association between ELS and aging; the second, measured the telomere length of older women associated with ELS and cognitive decline and the third, examined the impact of the interaction between Val66Met BDNF polymorphism X ELS on the memory of older women. RESULTS: The first section identified neuroendocrine, immune, epigenetic and cell modifications signaling ELS as an accelerator of aging. The second, found no shorter telomeres in older women who reported ELS, but confirmed the association between telomere shortening and cognitive decline. Data from the third section confirmed the interaction between Val66Met BDNF polymorphism X ELS reduce memory performance of older women. The studies suggest telomere shortening as a biomarker of cognitive performance in women, but not directly mediated by ELS. Also, the interaction between the Val66Met BDNF polymorphism X ELS was confirmed as a significant risk condition for impairment in memory performance of older women.